Evaluation of Pharmaceuticals Inventory Management in Selected Health Facilities of West Arsi Zone, Oromia, Ethiopia - Jobira T; Abuye H; Jemal A; Gudeta T (Dove Medical Press, 2021)
Tadesse Jobira,1 Habtamu Abuye,2 Awol Jemal,3 Tadesse Gudeta3 1Health Office Logistic Coordination, Shashemene City Administration, Shashemene, Ethiopia; 2Department of Pharmacy, College of Medicine and Health Sciences, Wachemo University, Hossaena, Ethiopia; 3Pharmaceutical Supply Chain Management Department, School of Pharmacy, Institute of Health, Jimma University, Jimma, EthiopiaCorrespondence: Habtamu AbuyeWachemo University, P.o. Box: 667, Hossaena, EthiopiaTel +251 913571974Fax +251-46-555-19-30Email harohabe@gmail.comBackground: Effective inventory management ensures an uninterrupted supply of safe, effective, and affordable pharmaceuticals which could be achieved through developing ABC-VEN (Always, Better, Control–Vital, Essential, Desirable) and FSN–XYZ (Fast, Slow, Non-moving–High, Medium, Low Value) matrix analysis. ABC–VEN matrix analysis is used to control inventory according to their annual consumption and on their functional importance whereas, FSN–XYZ matrix analysis is applied to control inventory by identifying the items to be discarded and the amount saved during the closing of annual accounts.Objective: To evaluate inventory management in selected health facilities of West Arsi zone, Oromia regional state for the year 2016– 2018.Methods: Facility-based cross-sectional descriptive study complemented with a qualitative study was conducted in fourteen health facilities. Data were collected from goods issuing vouchers for the year 2016– 2018 to perform ABC–VEN matrix analysis. The frequency of issue was collected to perform FSN analysis and the value of each closing stock was taken to get XYZ analysis.Results: From the ABC–VEN matrix analysis, 26.6% of items were Category I of which the highest proportion were taken by class A and V items consuming 84.7% of annual drug expenditure (ADE). The remaining 49.2% and 24.2% of the drugs accounted for only 13.2% and 2.1% of the ADE being category II and III, respectively. Based on FSN–XYZ matrix analysis findings, category I with 41.% item share account for the highest budget (average 86.5% of values). Of this category, the XN group—non-moving and high-cost drugs had the high value (20%) which need managerial measure. In category III, the ZN group items, being 25% of drugs, only had 2.2% of value—that may increase wastage, inventory holding cost, and shortage of storage space.Conclusion: The matrix analysis for inventory control is a strong tool that enables one to identify items requiring close monitoring. The coupled ABC–VEN matrix analysis, combining their individual advantages – inventory’s cost and its functional importance help in achieving a meaningful inventory management. However, to control the stock at an appropriate level with minimum shortage and oversupply, it has to be supported by XYZ–FSN matrix analysis. The XYZ–FSN matrix benefits the health facilities to determine the level of inventory with high value in dead-stock, and to take measures like transferring to others, discarding, or saving.Keywords: ABC–VEN matrix analysis, FSN–XYZ matrix analysis, inventory management